Bekämpningsmedelsrester i yt- och grundvatten i Vänerns avrinningsområde - förekomst och möjliga effekter på natur och människor - Bilén, Anna-Karin (2020)
In 2001 the Lake Vänern Society for Water Conservation¹ started a project about xenobiotics in lake Vänern. The present study is a part of that project and the aim was to collect information from investigations of pesticide residues in surface- and groundwater in the catchment area of lake Vänern. With the results in mind, possible effects on nature and on human beings are discussed.